(untitled) (Scientific journal of the Fergana State University, 2023)
Many physical processes, many problems of natural science, technology are brought to find an unknown function that describes the phenomenon or process under consideration. When solving such practical problems, it is necessary to calculate the values ​​of various order derivatives of the function given in the form of a table or a complex analytical expression. In such cases, it is either impossible to apply differential calculus methods, or it is very difficult. Therefore, approximate numerical methods are used for them. One of these methods is the Runge-Kutta method, which, despite its laboriousness, solves differential equations is widely used in computer numerical solutions.In this article, the result was solved by the Runge-Kutta method, which is considered one of the high-accuracy methods of numerically solving the differential equation (Cauchy problem) given with the initial conditions, in the Maple program.